Utilizing of transceiver method to identify water and oil flow regime using ultrasonic tomography - Mohd Norhafizzi, Sidek (2012)
Tomography refers to imaging by sections or sectioning, through the use of any kind of penetrating wave. From point of view, process tomography refers to a method of acquiring the internal characteristics of pipelines flows or process vessel reaction from the measurement on the domain of interest. On recent years, the applications of tomography techniques were used by various fields such as in medical and also industrial process as it advantages to the system. For this project,both hardware and software used to demonstrate the system; hence the component in pipeline vessels can be analyzed. For the hardware part, it consists of ultrasonic sensor setup and electronic measurement setup which generate the pulse from the sensors through the pipeline. The output from the experiment was discussed and analyzed using oscilloscope. The purpose of this project is to develop a suitable ultrasonic tomography system for the pipeline. This project will produce 8x8 projections (8-transceiver) with utilizing of transceiver method for two phase flow regime identification. As a result, the identifying of water and oil flow regime can be analysis.